2013
DOI: 10.1681/asn.2012060550
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxins Attenuate Renal Fibrosis by Inducing let-7c and Suppressing TGFβR1

Abstract: Lipoxins, which are endogenously produced lipid mediators, promote the resolution of inflammation, and may inhibit fibrosis, suggesting a possible role in modulating renal disease. Here, lipoxin A4 (LXA 4 ) attenuated TGF-b1-induced expression of fibronectin, N-cadherin, thrombospondin, and the notch ligand jagged-1 in cultured human proximal tubular epithelial (HK-2) cells through a mechanism involving upregulation of the microRNA let-7c. Conversely, TGF-b1 suppressed expression of let-7c. In cells pretreated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
138
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(145 citation statements)
references
References 46 publications
7
138
0
Order By: Relevance
“…Several molecules were proposed to be involved in the profibrotic switch of fibroblasts (or pericytes) during renal fibrosis, including the Wnt signaling pathway (e.g., Wnt4, LRP-6, and DKK-1) (183,184), oxidative stress and NADPH oxidase (39,88,185), integrins including aV integrin (186), Rheb/mTORC1 signaling (187) as well as lipid mediators, including prostaglandins and their receptors like EP4 (188,189), prostacyclins (190), or lipoxins (191,192).…”
Section: The Role Of Interstitial Mesenchymal Cellsmentioning
confidence: 99%
“…Several molecules were proposed to be involved in the profibrotic switch of fibroblasts (or pericytes) during renal fibrosis, including the Wnt signaling pathway (e.g., Wnt4, LRP-6, and DKK-1) (183,184), oxidative stress and NADPH oxidase (39,88,185), integrins including aV integrin (186), Rheb/mTORC1 signaling (187) as well as lipid mediators, including prostaglandins and their receptors like EP4 (188,189), prostacyclins (190), or lipoxins (191,192).…”
Section: The Role Of Interstitial Mesenchymal Cellsmentioning
confidence: 99%
“…Recently, it was found that under normal conditions, let-7 maintains low levels of TGF-␤R1 expression in human umbilical vein endothelial cells and in adult human liver cells (30,31). In addition, in tubular epithelial cells, lipoxins were shown to down-regulate TGF-␤R1-induced fibrosis by up-regulating let-7c (32). Another recent paper also showed that let-7b targets TGF-␤R1 related to kidney fibrosis (33).…”
Section: Micrornas (Mirnas)mentioning
confidence: 99%
“…1, A-C). Recent reports have identified TGF-␤R1 as a target of let-7c and let-7b in renal cells (30,32,33). Interestingly, computational analysis using Target Scan software identified TGF-␤R1 as a potential profibrotic target of not only let-7b but also the other two miRNAs, miR-130b and miR-30e*.…”
Section: Decreased Expression Of Mir-130b and Let-7b In Tgf-␤1-treatementioning
confidence: 99%
See 1 more Smart Citation
“…[33][34][35] More recently, LXA 4 exhibited antifibrotic properties by upregulation of let-7c expression in renal fibrosis. 36 However, whether LXA 4 augments AFC through a particular miRNA in LPS-induced ALI, and if so, what the underlying mechanisms are remain unclear.…”
mentioning
confidence: 99%